Feasibility and effectiveness of healthy menu changes for non-trainee military dining facilities - Belanger, Bethany Ann (Kansas State University, 2014)
The purpose of this study was to assess the food choices and consumption of soldiers and their satisfaction with current and initial military training (IMT) menu standards through a survey and analysis of food selection and consumption. Participants were recruited during lunch periods before and three weeks after implementing IMT menu standards, which are healthier than current menu standards, in an Army dining facility (DFAC). Direct observations, digital photography, and plate waste methods were used to assess soldiers’ food selection and consumption. A survey was also administered to determine soldiers’ attitudes toward health, nutrition knowledge, reported food selection and consumption behaviors, and overall satisfaction with meals served under the two menu standards. Food selection and consumption were evaluated using the Army’s Go for Green Nutrition Labeling Program and the Military Dietary Reference Intakes (MDRIs). Descriptive and inferential statistics were calculated to summarize and compare data, and to identify potential associations among variables. A total of 172 and 140 soldiers participated before and after the menu change, respectively. Soldiers’ food selection patterns were similar to the proportion of green-, yellow-, and red-labeled items offered in the DFAC under both menu standards and significantly improved after the intervention (p<0.001). Soldiers consumed 886 kcal (38.6% from total fat and 11.2% from saturated fat) and 1784 mg of sodium before the menu change. Three weeks after the change, all figures improved (705 kcals, 31% of kcals from total and 9% from saturated fat, and 1339 mg of sodium) (p<0.01). Overall satisfaction and meal acceptability before and after the intervention were not different, and “food appeal” ratings actually improved. With the exception of sugar-sweetened beverage consumption, attitudes toward health were significantly associated with all reported food behaviors (p<0.01) but not with actual behaviors (p>0.05). Nutrition knowledge significantly influenced some but not all aspects related to attitudes toward health. Perceived hunger levels were positively associated with intakes of calories, protein, total fat, sodium, and cholesterol (p<0.05). Findings suggest that implementing the IMT menu standards in non-trainee Army DFACs is feasible and has the potential to improve the overall healthfulness of soldiers’ food selection and consumption.
Keywords: U.S. military; Customer satisfaction; Healthy menus; Nutrition quality; Obesity; Nutrition (0570)